EASIX and Severe Endothelial Complications After CD19-Directed CAR-T Cell Therapy—A Cohort Study - Korell, Felix; Penack, Olaf; Mattie, Mike; Schreck, Nicholas; Benner, Axel; Krzykalla, Julia; Wang, Zixing; Schmitt, Michael; Bullinger, Lars; Müller-Tidow, Carsten; Dreger, Peter; Luft, Thomas (Frontiers in Immunology, 2022)
Background: Endothelial dysfunction is associated with two main complications of chimeric antigen receptor T (CAR-T) cell therapy, cytokine release syndrome (CRS) and immune effector cell-associated neurotoxicity syndrome (ICANS). This study evaluates the Endothelial Activation and Stress Index (EASIX) as prognostic marker for high-grade CRS and ICANS in patients treated with CD19-directed CAR-T cells. Methods: In this retrospective study, a training cohort of 93 patients from the ZUMA-1 trial and a validation cohort of 121 patients from two independent centers (University Hospital Heidelberg, Charité University Medicine Berlin) were investigated. Primary objective was to assess the predictive capacity of EASIX measured immediately before start of lymphodepletion (EASIX-pre) for the occurrence of grade ≥3 CRS and/or ICANS. To explore a possible endothelial link, serum levels of endothelial stress markers (angiopoietin-2, suppressor of tumorigenicity-2, soluble thrombomodulin, and interleukin-8) were determined before lymphodepletion and on day 7 after CART infusion in the validation cohort (n=47). Results: The prognostic effect of EASIX-pre on grade ≥3 CRS and/or ICANS was significant in the training cohort (OR 2fold increase 1.72 (1.26-2.46)) and validated in the independent cohort. An EASIX-pre cut-off >4.67 derived from the training cohort associated with a 4.3fold increased odds ratio of severe CRS/ICANS in the independent cohort. Serum endothelial distress markers measured on day+7 correlated with EASIX-pre and associated with severe complications. Conclusions: EASIX-pre is a powerful predictor of severe CRS/ICANS after CD19-directed CART therapy and might be used as a basis for risk-adapted prevention strategies. Conclusions: EASIX-pre is a powerful predictor of severe CRS/ICANS after CD19-directed CART therapy and might be used as a basis for risk-adapted prevention strategies.